The Effect of Visual Auditory Kinesthetic Learning Model on Arabic Learning Achievement in Grade VII Junior High School: Pengaruh Model Pembelajaran Visual Auditori Kinestetik Terhadap Prestasi Belajar Kelas VII SMP - Yuni Rahmawati; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2021)
This research aimed to Knowing the effect of using visual, auditory, and kinesthetic learning models on the Arabic learning achievement in class VII students of SMP Muhammadiyah 3 Waru. This type of research is field research, the nature of the research is correlation, with a quantitative approach. Data were collected using questionnaire techniques, observation and documentation, and also from the list of students' scores. After the data is analyzed using the product moment formula, The results obtained from the correlation coefficient between variable X and variable Y are 0.7187, or 51.65%. From these results, the visual, auditory, and kinesthetic learning models have a great influence on the learning achievement of Arabic for class VII SMP Muhammadiyah 3 Waru.